Relationship of Serum Leptin Level with Chronological Age and Body Mass Index in Adolescent Girls - Ather, Uzma; Shirwany, Tanvir Ali Khan; Imran, Irum; Saleem, Muhammad; Gul, Farah; Saleem, Azka; Zafer, Javeria (Annals of King Edward Medical University, 2018)
Objective: The study aimed to evaluate the effect of chronological age and Body Mass Index (BMI) on concentration of leptin in serum. Methods: It is a cross-sectional comparative study. One hundred and fifty two girls were selected from different schools in Lahore. Their demographic data was recorded. The sample was divided into 10 groups, comprising approximately 15 girls in each age group with age range of 8.0 to 17.99 years. Their height and weight were measured to determine their BMI. Blood samples were collected to determine the serum leptin level by Enzyme Linked Immunosorbent Assay (ELISA) method. Pearson correlation test were applied to observe the correlation between serum leptin and BMI. Results: The mean BMI is 18.20±3.70 kg/m2 and mean serum leptin value is 6.653±7.11 ng/ml over all groups. A positive correlation was observed between serum leptin and chronological age, (r = 0.225, and p <0.005). A strong positive correlation was observed between BMI and serum leptin concentration (r = 0.604, P<0.000). The mean BMI in underweight, normal weight and overweight subjects were 14.35±1.63 kg/m2, 17.85±2.45 kg/m2, 24.08±2.98 kg/m2, and mean serum leptin concentrations 3.28±3.90 ng/ml, 5.32±5.46 ng/ml, 16.42±8.39 ng/ml respectively (r = 0.511, and p <0.000) . Conclusion: Serum leptin level is positively correlated with chronological age and BMI. This study indicates that serum leptin increases with advancement in chronological age and higher BMI results in higher serum leptin level.